Advances in improving tolerance to waterlogging in Brachiaria grasses - Cardoso Arango, Juan Andrés; Jiménez, J.; Rincón, J.; Guevara, Edward D.; Hoek, Rein van der; Jarvis, Andy; Peters, Michael; Miles, John W.; Ayarza, Miguel Angel; Cajas, S.; Rincón, A.; Mateus, H.; et al. (International Center for Tropical Agriculture, 2013)
An inter-institutional and multi-disciplinary project to identify *Brachiaria* genotypes, which combine waterlogging tolerance with high forage yield and quality, for use in agricultural land in Latin America with poor drainage, is underway. The aim is to improve meat and milk production and mitigate the impacts of climate change in the humid areas of Latin America. Researchers at the International Center for Tropical Agriculture (CIAT) have developed a screening method to evaluate waterlogging in grasses. Using this method, 71 promising hybrids derived from the species, *Brachiaria ruziziensis*, *B. brizantha* and *B. decumbens*, were evaluated. Four hybrids with superior waterlogging tolerance were identified. Their superiority was based on greater: green-leaf biomass production, proportion of green leaf to total leaf biomass, green-leaf area, leaf chlorophyll content and photosynthetic efficiency; and reduced dead-leaf biomass. These hybrids, together with previously selected hybrids and germplasm accessions, are being field-tested for waterlogging tolerance in collaboration with National Agricultural Research Institutions and farmers from Colombia, Nicaragua and Panama.